QUALITY MANAGEMENT BASED ON CHARACTER EDUCATION IN THE MILLENNIAL ERA IN BUILDING STUDENT INDEPENDENCE - Nuryani, Lilis Kholisoh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to find out muslim student independence guidance model based on Islamic characters. The model used in this research is 4D (define-design- develop-disseminate) research and development with quantitative and qualitative data analysis technique in a situation of guidance for muslim students of Ar-Risalah Islamic Boarding School Ciamis, Indonesia. Results of the research show that muslim student character development is based on teaching, habituation and enforcement processes of rules based on curriculum. The guidance model is based on quality management by applying Plan-Do-Check-Action (P-D-C-A-cycle) process which is implemented and accustomed by students in a daily manner. The independence guidance is conducted through PDCA cyrcle which is focused on willingness to learn, responsibility in each learning activity, ability for decision making, self-confidence and bravery. Meanwhile, there are also Islamic characteristics that are accustomed and implemented namely sidiq (being honest), tabligh (delivering), amanah (reliable) and fatonah (smart). Recommendation for this model trial is that it is necessary for strategies to support more willingness to learn and implement fatonah character.